2005
DOI: 10.1177/194589240501900202
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Interleukin-5, Interleukin-8, and Interleukin-10 mRNA in the Osteomeatal Complex in Nasal Polyposis

Abstract: IL-5 cytokine expression in the osteomeatal complex is linked to the presence of nasal polyps, whereas IL-8 is up-regulated without distinct correlation to nasal polyps. IL-10 expression was detectable in five of eight allergic patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
22
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 22 publications
2
22
0
Order By: Relevance
“…Elevated levels of IL-8 have been implicated in the formation of scar in adult skin tissue [11]. Additionally, IL-8 was elevated in chronic rhinosinusitis and nasal polyps [10,21]. Our present study indicated that IL-6 and IL-8 levels were significantly increased in regenerative mucosa, and the levels of IL-6 and IL-8 in the wound had a significant correlation with the level of collagen type I.…”
Section: Discussionsupporting
confidence: 47%
“…Elevated levels of IL-8 have been implicated in the formation of scar in adult skin tissue [11]. Additionally, IL-8 was elevated in chronic rhinosinusitis and nasal polyps [10,21]. Our present study indicated that IL-6 and IL-8 levels were significantly increased in regenerative mucosa, and the levels of IL-6 and IL-8 in the wound had a significant correlation with the level of collagen type I.…”
Section: Discussionsupporting
confidence: 47%
“…IL-12 is the most significant cytokine in the transformation of Th0 cells to Th1 cells. However, scholars have demonstrated that IL-10 is highly expressed in nasal polyp tissues (21). DCs are not only able to secrete IL-10 themselves but are also able to induce T cells to secrete IL-10 (15).…”
Section: Discussionmentioning
confidence: 99%
“…Invitro effects of RANTES on eosinophils include chemotaxis, transendothelial migration, induction and production of reactive oxygen, and the release of ECP [28]. IL-8 is predominantly a chemoattractant for neutrophils as well as for eosinophils after these target cells have been primed with IL-5 [21,26]. Positive correlations between concentration of IL-2 and nasal symptom score, endoscopic score and Lund-Mackay score is difficult to explain.…”
Section: Discussionmentioning
confidence: 99%
“…IL-10 is an anti-inflammatory Th2 cytokine produced by T-lymphocytes, monocytes and macrophages. It is considered to inhibit the release of IFN-c and the cytokine synthesis of monocytes and leads to marked immunosupression [26].…”
Section: Discussionmentioning
confidence: 99%